2023
DOI: 10.1007/s11938-023-00428-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Diagnosis and Response Evaluation in Patients with Eosinophilic Esophagitis

Abstract: Purpose of review The aim of this review is to provide practical guidance for clinicians to support the optimal use of endoscopy in both the diagnosis and the evaluation of treatment response in patients with eosinophilic esophagitis (EoE). Recent findings The systematic and high-quality assessment and grading of EoE endoscopic features improves EoE detection. Fibrotic complications of EoE that negatively impact patients’ symptoms and quality of life can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…In this study, there was good correlation between endoscopic findings suggestive of EoE and the presence of eosinophilic infiltrate and, in accordance with other studies, the presence of more than one endoscopic abnormality is strongly suggestive of EoE (12)(13)(14)(15)(17)(18)(19) . Edema, whitish exudates, and vertical lines are useful to identify EoE, and a score comprising these findings can be highly predictive of esophageal eosinophilia, particularly in children.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, there was good correlation between endoscopic findings suggestive of EoE and the presence of eosinophilic infiltrate and, in accordance with other studies, the presence of more than one endoscopic abnormality is strongly suggestive of EoE (12)(13)(14)(15)(17)(18)(19) . Edema, whitish exudates, and vertical lines are useful to identify EoE, and a score comprising these findings can be highly predictive of esophageal eosinophilia, particularly in children.…”
Section: Discussionsupporting
confidence: 92%
“…The studies, that showed better sensitivity of the endoscopic findings, had selected patients after PPI treatment, following the previous criteria for diagnosis of EoE that required a failed response to PPI to establish the diagnosis (13,(15)(16)(17)(18)26,29) . PPI have both anti--inflammatory and anti-secretory actions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations